Studi Identifikasi Indeks Kekeringan Hidrologis Pada Daerah Aliran Sungai (DAS) Berbasis Sistem Informasi Geografis (SIG) (Studi Kasus pada DAS Brantas Hulu : Sub-DAS Upper Brantas, Sub-DAS Amprong dan Sub-DAS Bangosari) - Sholikhati, Ima; Harisuseno, Donny; Suhartanto, Ery (Fakultas Teknik, Universitas Brawijaya, 2013)
Drought is a natural hazard which is characterized by the scarcity of water. Drought disaster management with non-structural approach through drought monitoring with drought spatial information in monthly drought index map and temporal information for each region in sub-watershed. The location of research is Upstream Brantas River Basin which is divided into 3 (three) sub catchments supplemented with 12 (twelve) selected rainfall stations capable of sending real-time daily rainfall data. The analysis of this drought uses Thornthwaite and Mather’s (1957) method, which is an index to inform the drought rate of a region by using water balance parameter. Result of study indicates that the biggest drought index is found in years of 1991, 1994, 1997, 2002 and 2008 (during the happening of El-Nino) from July to October. This high drought index seems following the decrease of the discharge at Gadang AWLR in those years.Keywords: Drought Index, Thornthwaite, El-Nino, Water Balance, Climate Change